Digital Campaign to Reduce Covid-19 Pandemic Risk - Naryoso, Agus; Febriyani, Arifa Rachma; Kaloka, Rintulebda Anggung (Universitas Muhammadiyah Yogyakarta, 2021)
Hoaxes about COVID-19 on social media could be seen publicly and intentionally lead to inappropriate responses amid the pandemic. In this situation, the government’s public relations had a role in educating the public through accurate information about COVID-19 on social media. This research aimed to describe the public’s attitude towards digital campaigns to reduce the risk of COVID-19 in Central Java and the strategy behind this digital campaign. The research was designed as a descriptive study with a mixed approach method. The sampling technique used was purposive sampling. The data was collected through an online survey of 121 respondents, interviews with expert sources, and document review. Elaboration Likelihood Theory and Rhetoric Theory are used to explain the digital campaign. The results showed that most respondents (74%) rated the Governor as prioritizing the positive appeal approach through a digital campaign. The interview results revealed that the process of composing creative content in the digital campaign was carried out through discussions between the Governor and the content creator team. During a pandemic, a creatively packaged digital campaign was a strategic step to increase public participation in implementing preventive efforts.